Detection of Histone Modifications at Specific Gene Loci in Single Cells in Histological Sections - Gomez, Delphine (2013)
Chromatin immunoprecipitation (ChIP) assays have contributed greatly to our understanding of the role of histone modifications in gene regulation. However, a major limitation is that they do not permit analysis with single cell resolution thus confounding analyses of heterogeneous cell populations. Herein we present a new method which permits visualization of histone modifications of single genomic loci with single-cell resolution in formaldehyde-fixed paraffin-embedded tissue sections based on combined use of In Situ Hybridization (ISH) and Proximity Ligation Assays (PLA). Using this method we show that H3K4dime of the MYH11 locus is restricted to the smooth muscle cell (SMC) lineage in human and mouse tissue sections, and that the mark persists even in phenotypically modulated SMC within atherosclerotic lesions that show no detectable expression of SMC marker genes. This new methodology has promise for broad applications in the study of epigenetic mechanisms in complex multicellular tissues in development and disease.